Emotions Across Cultures : Ancient China and Greece. - Konstan, David. (Roma Sinica Series, 2022)
Roma Sinica. Mutual interactions between Ancient Roman and Eastern Thought is an original series in classical and comparative studies. Generously supported by the SIAC (International Society of Cicero's friends), it aims to publish works concerning the relationships between Ancient Western (Greek, Roman) and Eastern (Korean, Chinese, Japanese) thought.